Shelf-derived mass-transport deposits: origin and significance in the stratigraphic development of trench-slope basins. Issue 1 (2nd January 2022) - Claussmann, Barbara; Bailleul, Julien; Chanier, Frank; Mahieux, Geoffroy; Caron, Vincent; McArthur, Adam D.; Chaptal, Corentin; Morgans, Hugh E. G.; Vendeville, Bruno C.
ABSTRACT: Continental shelves generally supply large-scale mass-wasting events. Yet, the origin and significance of shelf-derived mass-transport deposits (MTDs) for the tectonostratigraphic evolution of subduction complexes and their trench-slope basins have not been extensively studied. Here, we present high-resolution, outcrop-scale insights on both the nature of the reworked sediments, and their mechanisms of development and emplacement along tectonically active margins, by examining the Middle Miocene shelf-derived MTDs outcropping in the exhumed southern portion of the Hikurangi subduction margin. Results show that periods of repeated tectonic activity (thrust propagation, uplift) in such compressional settings not only affect and control the development of shelfal environments but also drive the recurrent generation and destruction of oversteepened slopes, which in turn, favour the destabilisation and collapses of the shelves and their substratum. Here, these events produced both large-scale, shelf-derived sediment mass-failures and local debris flows, which eventually broke down into a series of coalescing, erosive, genetically linked surging flows downslope. The associated MTDs have a regional footprint, being deposited across several trench-slope basins. Recognition of tectonic activity as another causal mechanism for large-scale shelf failure (in addition to sea-level changes, high-sedimentation fluxes) has implications for both stratigraphic predictions and understanding the tectonostratigraphic evolution of deep-marine fold-and-thrust belts.